Resource Center SLB Sidomulyo: Implementasi Sekolah Inklusif di Lampung Selatan - Siti Nurjannah (Journal of Public Policy Analys, 2023)
This study describes the development of the Sidomulyo State SLB Resource Center (RC)’s current role towards implementing inclusive schools in South Lampung based on policies issued by the government through Permendiknas number 70 of 2009 and PP number 13 of 2020. In the South Lampung area, there are two inclusive schools, SDN 1 Kalianda and SMPN 2 Kalianda, as well as 1 State SLB and 2 Private SLBs, which are recorded in the Dapodik database, namely State of SLB Sidomulyo, SLB Kasih Bunda, and SLB IT Harapan Bangsa. SLBN Sidomulyo is the only SLB that also has the role of RC in the South Lampung area. In general, RC has several tasks and roles that aim to improve the quality of inclusive school services. This research employs qualitative case study method. The results of the discussion in this study explain that, in RC SLBN Sidomulyo, the roles have not been carried out appropriately. As a result, inclusive schools at both the Elementary School (SD) and Junior High School (SMP) have been appointed by the local government not being properly implemented.